Inadequacy of nutrients in children’s diets across seasons along an agricultural intensification gradient in Ethiopia - Moges, Tibebu; Baudron, Frédéric; Luo, Hanqi; Brouwer, Inge D.; Remans, Roseline; Groot, Jeroen C. J. (Springer, 2024)
Although the production-to-consumption pathway is widely promoted to improve diet quality in developing world, its contribution to individual diet and nutrient intake remains unclear. We assessed this relationship among 377 children aged 6 to 59 months in three zones characterized by landscape diversity along an agricultural intensification gradient from the state forest of Munesa to the nearby town of Arsi Negele, Ethiopia during the two harvest seasons. A repeated interactive multiple-pass 24-h recall method was used to collect intake data. Usual intake distributions for energy, protein, iron, zinc and vitamin A were estimated using the National Cancer Institute (NCI) method and compared with estimated average requirement values to determine the prevalence of inadequate intake. The usual intake of protein, zinc and vitamin A among children were inadequate and further exacerbated by seasonality. The extent of nutrient inadequacy was higher in the diverse landscape (“near to forest” zone) than in the less diverse landscape (“distant to forest” zone). However, the diverse landscape tended to provide a better buffering capacity against seasonal energy and nutrient stress than a less diverse landscape. The age of a child positively predicted usual intakes of energy, protein, iron, zinc and vitamin A along the gradient, while breastfeeding negatively predicted these intakes. Most of the food groups and nutrients consumed were derived from on-farm production, whereas fruits and vegetables were via the market. Thus, introduction of nutrient-dense crops and increasing livestock productivity are vital to enhance consumption of diverse diets and thereby nutrients among children.